Strategi Penggunaan Teknologi Pendidikan dan Dampak Yang Mempengaruhi Pemanfaatan Teknologi di SD Negeri Tambula - Muttaqin, Ahmad Lutfian; Hasyim, M. Ishak; Febiola, Helena; Salsabila, Unik Hanifah (TSAQOFAH, 2022)
Information technology is a rank that is used by a person to process data, obtain information and so on. This greatly affects the environment in society and has a negative and positive impact depending on how someone uses it as well as the people in the surrounding environment. utilizing information technology in everyday life, not only among young people, even housewives also use technology including cellphones, gadgets, and computers and this has a positive impact on them, especially for those who have a myriad of activities inside and outside environment, with super busy activities, of course, young people are tired of choosing things that are instant and fast, namely by using information technology. The development of information technology in society turns out to have so many effects, both young and old, namely where technology makes it easier for them to do instant work, for example, if they buy an item that they don't need to bother with using only cellphones or gadgets, they can buy goods that they want without having to come to the store this has saved time, so without information technology everything we do can become an instance without having to waste time with no benefits.